1993
DOI: 10.1007/bf02928184
|View full text |Cite
|
Sign up to set email alerts
|

Using computer-based readers to improve reading comprehension of students with dyslexia

Abstract: Twenty-eight middle school students, diagnosed as dyslexic and attending a school using the Slingerland approach to remediation of dyslexia, used a computer-based reading system for reading literature for about one-half hour a day for a semester. The system proved to be a strong compensatory aid, enabling 70 percent of the students to read with greater comprehension, approximately one grade level or more improvement, as measured by the Gray Oral Reading Test. For 40 percent of the students, the gains were larg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
43
0
1

Year Published

1995
1995
2018
2018

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(48 citation statements)
references
References 4 publications
4
43
0
1
Order By: Relevance
“…Students with low scores on unassisted reading comprehension scores showed the most growth when using assistance while those with relatively high unassisted reading scores showed no growth, or poorer performance when using the speech synthesis. Elkind, Cohen, and Murray (1993) found a similar pattern with the same technology. In the current study an inverse correlation existed but it was not significant (-.338, p=.067).…”
Section: Results Of the Paired Sample Test Of Comparisons Of The Withsupporting
confidence: 61%
See 1 more Smart Citation
“…Students with low scores on unassisted reading comprehension scores showed the most growth when using assistance while those with relatively high unassisted reading scores showed no growth, or poorer performance when using the speech synthesis. Elkind, Cohen, and Murray (1993) found a similar pattern with the same technology. In the current study an inverse correlation existed but it was not significant (-.338, p=.067).…”
Section: Results Of the Paired Sample Test Of Comparisons Of The Withsupporting
confidence: 61%
“…Higgins and Raskind (1997), as well as Elkind, Cohen, and Murray (1993) have shown that speech synthesis, in combination with optical character recognition, improved comprehension of college students with severe reading deficits. Both studies also found that there was a significant inverse correlation between silent reading score without assistance and amount of improvement in scores when using SS/OCR.…”
Section: Discussionmentioning
confidence: 99%
“…Higgins and Raskind (1997) obtained a similar result. In an earlier study, Elkind, Cohen, and Murray (1993) found an enhancement of comprehension in a study of middle school students. Leong (1992) studied the effects of text-to-speech systems on reading comprehension of elementary school students in a task in which the students were given word knowledge training.…”
Section: Introductionmentioning
confidence: 95%
“…For example, Elkind et al [4] report on the usefulness of text-to-speech systems to improve reading comprehension of students with dyslexia but their paper is more focused on the area of generic educational tools to help access text rather than providing a focused CALL environment. The Kar2ouche Shakespeare range [6] provides programs that present text and audio from Shakespeare's plays with the complete character set and a variety of backgrounds, props and sound effects.…”
Section: State-of-the-art In Randd and Applicationmentioning
confidence: 99%